Regiment Band Goes Foreign at FCB Awards - Joseph, Terry (Express)
Guests at the Maestro Extraordinaire Awards were upset at the repertoire performed by the Regiment Band, at a tribute to ten local veteran vocalists. The function was in celebration of long-standing performers of Calypso, Parang, Qwesh and Indian classical music. The Regiment Band confined itself to foreign music and played standards like ‘The Shadow of Your Smile’ and also performed songs by R. Kelly and Ricky Martin.
Keywords: Steel band music -- Trinidad and Tobago; Music -- Performance; Musicians -- Trinidad and Tobago